Agreement between activated partial thromboplastin time and anti-Xa activity in critically ill patients receiving therapeutic unfractionated heparin. Issue 175 (March 2019) - Ratano, Damian; Alberio, Lorenzo; Delodder, Frederik; Faouzi, Mohamed; Berger, Mette M.
Abstract: Background: No study supports the use of either aPTT or anti-Xa activity for heparin monitoring in critical care patients. There are no strong data on the agreement between aPTT and anti-Xa. The aims of this study were to: 1. Analyse the agreement between aPTT and anti-Xa in a large population of critically ill patients under unfractionated heparin therapy (UFH), 2. Identify clinical and biological factors associated to agreement or disagreement, and 3. Analyse the impact of anti-Xa availability on the use of aPTT and UFH therapy. Methods: Retrospective study in a 35 beds mixed-ICU population between 2006 and 2016 in a University teaching hospital. Inclusion criteria: delivery of a UFH dose >15, 000 U/24 h during at least one day with one anti-Xa determination. Data : demographic variables, aPTT, anti-Xa, laboratory variables, presence of extracorporeal devices (ECD). Pairs of simultaneously dosed aPTT and anti-Xa [aPTT:anti-Xa] were analysed on the basis of their agreement within the sub-therapeutic, therapeutic (aPTT 50–80″, anti-Xa 0.3–0.7 U/ml) or supra-therapeutic ranges. Results: 2283 patient admissions (2085 patients) were analysed. 35, 595 [aPTT:anti-Xa] pairs were found. The overall [aPTT:anti-Xa] agreement was 59.6% and lowest (54.3%) in presence of ECD compared to non-ECD patients (61.6%; p < 0.001). Sixteen demographic and biological variables were analysed and were not predictive of [aPTT:anti-Xa] agreement. No significant difference in administered UFH dose was observed after anti-Xa introduction. Conclusion: In this large cohort, the [aPTT:anti-Xa] agreement is <60% and significantly lower in patients with ECD. None of the variables identified as potentially affecting the agreement were predictive. Availability of anti-Xa had neither effect on aPTT use nor on UFH-dose. These results call for a prospective study to determine the optimal UFH-therapy monitoring tool. Highlights: In critically ill patients treated with UFH, agreement between aPTT and anti-Xa is <60%. Agreement is significantly lowered by the use of extracorporeal devices (ECD). No biological or demographic factors are predictive of agreement. The use of anti-Xa assay does not modify the dose of UFH delivered to patients on ECD.